The body in the reservoir : murder & sensationalism in the South - Trotti, Michael Ayers (University of North Carolina Press, 2008)
This book covers mass media and the sensational crime. Centered on a series of dramatic murders in nineteenth- and early twentieth-century Richmond, Virginia, "The Body in the Reservoir" uses these gripping stories of crime to explore the evolution of sensationalism in southern culture. In Richmond, as across the nation, the embrace of modernity was accompanied by the prodigious growth of mass culture and its accelerating interest in lurid stories of crime and bloodshed